2013
DOI: 10.1103/physrevlett.111.067601
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and Polarizing Nuclear Spins with Double Resonance on a Single Electron Spin

Abstract: We report the detection and polarization of nuclear spins in diamond at room temperature by using a single nitrogen-vacancy (NV) center. We use Hartmann-Hahn double resonance to coherently enhance the signal from a single nuclear spin while decoupling from the noisy spin bath, which otherwise limits the detection sensitivity. As a proof of principle, we (i) observe coherent oscillations between the NV center and a weakly coupled nuclear spin and (ii) demonstrate nuclear-bath cooling, which prolongs the coheren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
318
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(329 citation statements)
references
References 32 publications
4
318
1
6
Order By: Relevance
“…These effects have been neglected here for simplicity, but exploring these effects in the context of the phonon antenna mechanism could lead to an even more sophisticated principle, involving transient, broadband sampling of the spectral function and evolving exciton spectra and localisation lengths which could, potentially, activate or deactivate relaxation pathways dynamically. Finally, the concept of using coherent interactions to alter the sampling of a (fixed) environmental spectral function could be readily achieved in a variety of atomic and condensed matter systems [33,37], and could also be used as a sensitive probe for measuring spectral functions by measuring transport rates as functions of a controllable coupling parameter.…”
Section: Local Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects have been neglected here for simplicity, but exploring these effects in the context of the phonon antenna mechanism could lead to an even more sophisticated principle, involving transient, broadband sampling of the spectral function and evolving exciton spectra and localisation lengths which could, potentially, activate or deactivate relaxation pathways dynamically. Finally, the concept of using coherent interactions to alter the sampling of a (fixed) environmental spectral function could be readily achieved in a variety of atomic and condensed matter systems [33,37], and could also be used as a sensitive probe for measuring spectral functions by measuring transport rates as functions of a controllable coupling parameter.…”
Section: Local Energiesmentioning
confidence: 99%
“…a different electron or nuclear spin). This problem may be overcome by continuous driving of the electron spin in the sensor at a strength that leads to a splitting of dressed states that matches the externally generated signal and thus permits a strong response of the sensor (transitions between upper and lower dressed state) [33][34][35].…”
Section: Local Energiesmentioning
confidence: 99%
“…25,[39][40][41][42][43][44][45][46] At the same time, an alternative approach based on the continuous dynamical decoupling has been extensively investigated. 11,[47][48][49][50][51][52][53][54][55][56][57][58] Within this approach, strong resonant driving is applied to the NV center. The resulting fast Rabi oscillations of the NV spin, similarly to the flip-flops induced by the decoupling pulses, average out the interaction with the environment, and significantly extend the spin coherence time.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, polarization transfer to nuclei outside of the diamond itself still poses many challenges. It was also shown that nuclear polarization can improve NV based measurements, by increasing the NV spin free evolution/Ramsey coherence time [10]. …”
mentioning
confidence: 99%
“…NV based polarization of 13 C nuclei in the diamond can be achieved using the NOVEL (nuclear orientation via electron spin locking) scheme [11,12], allowing for nuclear sensing [10] and bulk polarization [13]. During this sequence a spin-lock [14] (SL) is applied on the NV spin with a SL Rabi frequency equal to the nuclear Larmor frequency, resulting in the rotating-frame/lab-frame Hartmann-Hahn polarization transfer condition.…”
mentioning
confidence: 99%